Photoinduced Copper‐Catalyzed Asymmetric Decarboxylative Alkynylation with Terminal Alkynes - Xia, Hai‐Dong; Li, Zhong‐Liang; Gu, Qiang‐Shuai; Dong, Xiao‐Yang; Fang, Jia‐Heng; Du, Xuan‐Yi; Wang, Li‐Lei; Liu, Xin‐Yuan (Angewandte Chemie International Edition, 2020)
We describe a photoinduced copper‐catalyzed asymmetric radical decarboxylative alkynylation of bench‐stable N‐hydroxyphthalimide(NHP)‐type esters of racemic alkyl carboxylic acids with terminal alkynes, which provides a flexible platform for the construction of chiral C(sp3)−C(sp) bonds. Critical to the success of this process are not only the use of the copper catalyst as a dual photo‐ and cross‐coupling catalyst but also tuning of the NHP‐type esters to inhibit the facile homodimerization of the alkyl radical and terminal alkyne, respectively. Owing to the use of stable and easily available NHP‐type esters, the reaction features a broader substrate scope compared with reactions using the alkyl halide counterparts, covering (hetero)benzyl‐, allyl‐, and aminocarbonyl‐substituted carboxylic acid derivatives, and (hetero)aryl and alkyl as well as silyl alkynes, thus providing a vital complementary approach to the previously reported method. Two in one: A photoinduced asymmetric radical decarboxylative alkynylation of bench‐stable racemic carboxylic acid derivatives with easily available terminal alkynes provides expedient access to diverse enantioenriched alkynes. The chiral copper catalyst serves as a dual photo‐ and cross‐coupling catalyst to achieve stereocontrol over the highly reactive prochiral alkyl radical intermediates.